KEBIJAKAN PENDIDIKAN DALAM MENINGKATKAN KOMPETENSI GURU SD TERPENCIL DI KABUPATEN SELUMA - Sutardi, Dodo (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
The performance of elementary school teachers in remote areas is still far from the standard, due to the efforts made not adaptive. Purpose of the research was to (1) develoving of BERMUTU learning model’s adaptive and (2) effectiveness of model BERMUTU learning’s adaptive in improving the performance of elementary school teachers at remote. The study was conducted at four remote elementary schools in Seluma Bengkulu Province. Have used two approaches: descriptive qualitative and metods of experimental with models noequivalent control group design. Results of the study: (1) BERMUTU learning model (learning based CAR) adapted to the limitations of teachers' academic qualifications, learning infrastructure, lack of training experience, low internal motivation (2) the model of BERMUTU learning’s adaptive more effective in improving the performance of elementary school teachers in remote village